2016
DOI: 10.1108/ejm-01-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Chinese cultural philosophies on the effects of employee friendliness, helpfulness and respectfulness on customer satisfaction

Abstract: Purpose This study aims to investigate the main and interactive effects of three employee attributes, namely, employee friendliness, helpfulness and respectfulness, on customer satisfaction in Mainland China. Design/methodology/approach A 2 × 2 × 2 between-subjects experimental design enabled an eight-scenario study depicting a service experience manipulated by employee friendliness (high/low), helpfulness (high/low) and respectfulness (high/low). Findings It is found that the effect of respectfulness has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 55 publications
(98 reference statements)
3
48
0
Order By: Relevance
“…How employees respond greatly influences customer interaction, called the "moment of truth" in managerial terminology. As empathy and helpfulness are directly linked to intrinsic motivation, as well as employee competency in performing a job (Liu et al, 2016), they are critical factors for determining the outcomes of service encounter moments of truth. About 50 per cent of the participants used words and phrases such as "understand my problems", "caring" and "pay special attention to my concerns" in their described critical incidents.…”
Section: P1 Customer Reciprocity Resulting From Delight and Beingmentioning
confidence: 99%
“…How employees respond greatly influences customer interaction, called the "moment of truth" in managerial terminology. As empathy and helpfulness are directly linked to intrinsic motivation, as well as employee competency in performing a job (Liu et al, 2016), they are critical factors for determining the outcomes of service encounter moments of truth. About 50 per cent of the participants used words and phrases such as "understand my problems", "caring" and "pay special attention to my concerns" in their described critical incidents.…”
Section: P1 Customer Reciprocity Resulting From Delight and Beingmentioning
confidence: 99%
“…FLEs usually represent the firm during service encounters, making them an integral part of service delivery (Keh et al, 2013;Liu et al, 2016). Thus, FLEs play critical roles in influencing customers' perceptions of service outcomes and firm effectiveness (Bettencourt and Brown, 1997;Bove et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In consumer research, warmth and competence perceptions have been shown to influence customers' attitudes and behaviors such as their satisfaction, purchase intention, word of mouth, loyalty and brand perceptions (Aaker et al, 2010;Castro et al, 2012;Keh et al, 2013;Liu et al, 2016;Wang et al, 2016). For example, customers' warmth and competence inferences operate differentially in customer-employee relationships depending on the salient communal versus exchange norms, which in turn influences their behavioral intentions (Scott et al, 2013).…”
Section: Warmth and Competence In Social Perceptionsmentioning
confidence: 99%
“…In this context, resilience and customer orientation (CO) represent interesting variables, since they can be enhanced through specific trainings [9,10]. To date, the majority of research has focused on customer perceptions [11], whereas only a few studies have analyzed this topic from the service provider perspective [12]. To date, only a few studies have examined the direct association between CO and SRP, with previous investigations on this topic predominantly concentrating on organizational-level CO [13][14][15].…”
Section: Introductionmentioning
confidence: 99%